Occurrence of Leaf-Cutting and Grass-Cutting Ants of the Genus Atta (Hymenoptera: Formicidae) in Geographic Regions of Brazil - Forti, L. C. [UNESP] (2020)
Leaf-cutting ants are widely distributed in Brazil, particularly species of the genus Atta. We therefore described the occurrence of leaf-cutting and grass-cutting ant species of the genus Atta. Five routes comprising some of the main highways in the South, Southeast, Midwest, and North of Brazil were sampled, in addition to ants received from other 82 municipalities, composing 300 municipalities sampled. This is the first comprehensive study of Atta in Brazil. The following species and subespecies were found: A. laevigata, A. capiguara, A. sexdens rubropilosa, A. sexdens piriventris, A. sexdens sexdens, and A. cephalotes. Atta laevigata and A. capiguara were the species present in the largest number of the Brazilian municipalities sampled. Atta sexdens piriventris was only recorded in the southern region of Brazil. Atta bisphaerica presented lower expansion than A. capiguara. Atta cephalotes and Atta opaciceps are species of very restricted occurrence. Southeastern region was characterized by the occurrence of A. capiguara and A. laevigata. Atta laevigata exhibited a generalized pattern of occurrence in the Midwest and North. Our study contributes to a better understanding of the so far unknown occurrence of leaf-cutting and grass-cutting ants within Brazil.